Assessing Profitability: The Impact of Selling Price Determination on the Revenue of Local Tofu Businesses - Amanda, Aprilia; Abidin, Zaenal; Khoiratun Nisak, Sayidah; Nilfatri; Pitri, Alisyah; Sarwono (CV. Civiliza Publishing, 2025)
Pricing strategy plays a crucial role in determining the success and sustainability of micro-enterprises, particularly in the food sector such as the tofu industry. This study aims to analyze the effect of selling price determination on the income of tofu producers in Dendang District, Jambi Province. Using a quantitative approach and data collected through questionnaires from 82 respondents, the results of linear regression analysis indicate that the selling price variable significantly influences income, with a coefficient of determination (R²) of 0.635. This suggests that 63.5% of the variation in income can be explained by the implemented pricing strategy. The novelty of this research lies in the integration of empirical analysis with an Islamic economic perspective, which emphasizes principles of fairness, transparency, and sustainability in business practices. The findings imply that the application of accurate and ethical pricing strategies not only enhances producers’ income but also supports broader goals of local economic development and community well-being.